1978
DOI: 10.1002/hlca.19780610324
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐katalysierte Isomerisierung von Butadien‐Hydrazon‐Misch‐Oligomeren. Vorläufige Mitteilung

Abstract: Nickel-catalysed Isomerization of Unsaturated Azocompounds SummaryUnsaturated azocompounds, produced by the nickel-catalysed reaction of butadiene with hydrazones, can be isomerized in presence of the same nickel catalyst. The influence of nickel concentration, temperature and structure of the azocompound on this rearrangement is described.Es ist bekannt, dass die nickel-katalysierte Misch-Oligomerisierung von Butadien mit Mono-alkyl-und -aryl-hydrazonen zu Azoverbindungen mit verzweigter oder h e a r e r Okta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…With extended reaction times the amount of the linear isomer F increases very strongly, which suggests an ensueing rearrangement E -F (12). Such a nickel-catalysed isomerisation of butadiene-oligomers has previously been described only for 1,2-divinylcyclobutane, which rearranges to 1,5-cyclooctadiene and 4-vinylcyclohexene (13).…”
Section: Introductionmentioning
confidence: 87%
“…With extended reaction times the amount of the linear isomer F increases very strongly, which suggests an ensueing rearrangement E -F (12). Such a nickel-catalysed isomerisation of butadiene-oligomers has previously been described only for 1,2-divinylcyclobutane, which rearranges to 1,5-cyclooctadiene and 4-vinylcyclohexene (13).…”
Section: Introductionmentioning
confidence: 87%
“…Isoprene formation is initiated by Ni -* C2 addition followed by rearrangement through a (cyclopropylmethyl)nickel intermediate (Scheme 5) while 1,4-hexadiene formation involves Ni -* C\ addition followed by C-C cleavage to give an r; 3 A rearrangement which might be related to those discussed above is the conversion of 3-substituted l,6(or l,7)-octadiene derivatives into the linear isomer (e.g. equation 21) 91 which is catalyzed by [Ni(cod) 2 ]-PPh 3 .…”
Section: Skeletal Rearrangementsmentioning
confidence: 97%
“…89 Octadienylated methylhydrazones have also been shown to be formed in a stoichiometric reaction between [NiPPh 3 (77 3 ,77 3 intermediates involved are possible and it has, moreover, been suggested that the /3-hydrogen transfer step occurs as a sigmatropic rearrangement within the complex without involving the nickel atom. 72 Complexes related to the intermediates shown in the Scheme have been isolated from the stoichiometric reaction between [Ni(cod)2], 1,3-dienes and Schiff bases.…”
mentioning
confidence: 99%